Telegraphy and Journalism in Colonial India, c. 1830s to 1900s - Bonea, Amelia (History compass, 2014)
This essay argues that a focus on technologies of communication such as the electric telegraph helps us to rethink the historiography of the press in colonial India by drawing attention to the ‘moments of transition’ of the 19th century and questioning dominant narratives of a media revolution spurred by telegraphy. It also enables us to overcome some of the limitations of previous nation-centric research by recovering the networks of technology and news which integrated newspapers during this period and providing insights into the development of news reporting in 19th-century India.